Analysis of temporal changes of microbiota diversity and environmental interactions in Saanen dairy goats - Liaoyu Fan; Jianing Shen; Xiang Li; Hengrui Li; Yuexin Shao; Christopher D. Lu; Huaiping Shi (Journal of Applied Animal Research, 2023)
Dynamic among animal, microbiota and environment can influence the health outcome of animals. Intensive production systems, with environmental challenges and implications, are increasing important due to land limitation and market demand especially in populous regions. Analysis of temporal changes of microbiota diversity will provide baseline information and contribute to animal welfare and health management in dairy goats raised under intensive systems and influence economic outcome. The analysis of changes in microbiota population over time is made possible by employing 16S rDNA amplicon sequencing technology. Our study documented these changes in dairy goats of various physiological stages raised under the enclosed environment.